Field Dependence-Independence and Eye Movement Patterns: Investigating Users' Differences Through an Eye Tracking Study - Nisiforou, Efi; Laghos, Andrew (My University, 2016)
The notion that users' characteristics such as the cognitive ability affect their visual information processing is continuously increasing. This eye tracking user study investigated the association between adults' ($N=54$) cognitive style and eye movement (EM) patterns while interacting with a set of visual tasks. Users' cognitive type was measured with the use of the Hidden Figures Test (HFT), which classifies them into field dependent (FD), field neutral (FN) and field independent (FI) individuals. Overall, the psychometric measures and the eye tracking-derived data were statistically examined revealing significant differences and large effect sizes among the two variables tested. Particularly, the findings demonstrated that the field dependence group exemplifies a more disoriented and disorganized EM activity. Hence, greater numbers of fixations and saccades are generated, contrary to the FN or FI users'. This research study adds further to the evidence and theory base of human-computer interaction for applications in the user-centred design by identifying how users' differences in cognitive style can be manifested in eye gaze patterns.
Keywords: Human–computer interaction; User cognitive type; Field dependence-independence; Eye tracking; Hidden figures tes; Embedded shapes; Eye movement patterns